Atomistic Modeling of Corrosion Resistance: A First Principles Study of O2 Reduction on the Al(111) Surface Covered with a Thin Hydroxylated Alumina Film. Issue 3 (19th March 2014) - Costa, Dominique; Ribeiro, Thomas; Mercuri, Francesco; Pacchioni, Gianfranco; Marcus, Philippe
<x xml:space="preserve">Abstract</x> In the early stage of corrosion of Al or Al alloys (i.e., during the initiation of localized corrosion), an oxide film is generally present on the surface. This work investigates the possibility for a cathodic reaction to occur on these oxide films. We discuss realistic models of supported oxide films on Al(111) in order to disentangle the factors determining the reactivity towards O2. Three components of the complex film formed on Al(111) can be identified: an ultrathin under‐stoichiometric AlxOy interface layer, an intermediate Al2O3 phase with γ‐alumina structure, and an hydroxylated AlOOH surface termination with boehmite structure. The electron transfer to O2 molecules depends on the workfunction, Φe, of the metal/oxide interface and on the thickness of the inner Al2O3 phase. The electron transfer takes place both from the metal‐oxide interface and the oxide surface to the adsorbed O2 molecule. Very important is the role of the hydroxyl groups at the surface: they eliminate the Al surface states and stabilize the surface; they allow the reduced O2− species to capture protons and transform into hydrogen peroxide in a non‐activated process. H2O2 is further reduced to two water molecules, in a series of two‐electron mechanisms. These reactions take place only when the internal alumina phase is ultrathin (here 0.2 nm). As soon as an Al2O3 inner layer develops (film thickness of about 1 nm), the film becomes unreactive and passivates the Al(111) surface. The results help to shed light on the complex reactions responsible for metal corrosion.